The Effect Of Leadership And Work Discipline On Employee Performance (Case Study Pt. Trans Indonesia Superkoridor Branch Tasikmalaya) - Pandu Pratama Maulana; Suci Putri Lestari; Ai Kusmiati Asyiah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to determine the simultaneous and partial influence of leadership and work discipline on employee performance at PT. Trans Indonesia Superkoridor branch Tasikmalaya. The research method used in this study is a quantitative method with a descriptive approach. The population of this study amounted to 53 employees PT. Trans Indonesia Superkoridor. The type of data used in this study uses validity tests, reliability tests and classic assumption tests. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of the study show that leadership and work discipline simultaneously have a significant effect on employee performance at PT. Trans Indonesia Superkoridor. Leadership partially has a significant effect on employee performance at PT. Trans Indonesia Superkoridor and Work Discipline partially has a significant effect on Employee Performance at PT. Trans Indonesia Superkoridor branch Tasikmalaya.